IR thermographic camera as useful and smart tool to analyse defects in organic solar cells - Przybył, Wojciech; Bogdanowicz, Krzysztof Artur; Jewłoszewicz, Beata; Dylong, Agnieszka; Dysz, Karolina; Iwan, Agnieszka; Januszko, Adam (Photonics Letters of Poland, 2020)
The main goal of this paper was to show that organic layers prepared for organic solar cells construction can be partially characterized by IR thermographic camera to detect dysfunctionalities of the active layer. Moreover, we used IR thermographic camera to check thermal and electrical behaviour of created simple solar cells to reduce time and cost in global production of solar cells. As model system organic compounds such as PTB7 polymer and small molecule PC71BM as commercial components and newly synthesized imine PV-BLJ-SC11 there were used, to construct simple devices. Full Text: PDF References K. D. G. I. Jayawardena, L. J. Rozanski, C. A. Mills, M. J. Beliatis, N. A. Nismy, S. R. P. Silva, "Inorganics-in-Organics’: recent developments and outlook for 4G polymer solar cells", Nanoscale, 2013, 5, 8411-8427. CrossRef Y. Lin, X. Zhan, "Oligomer Molecules for Efficient Organic Photovoltaics", Accounts of Chemical Research, 2016, 49, 175-183. CrossRef R. Steim, S. A. Choulis, P. Schilinsky, U. Lemmer, C. J. Brabec, "Formation and impact of hot spots on the performance of organic photovoltaic cells", Applied Physics Letters, 2009, 94, 043304. CrossRef J. Hepp, F. Machui, H. J. Egelhaaf, C. J. Brabec, A. Vetter, "Automatized analysis of IR‐images of photovoltaic modules and its use for quality control of solar cells", Energy Science and Engineering. 2016, 4, 363-371. CrossRef H. Hoppe, J. Bachmann, B. Muhsin, K. H. Drüe, I. Riedel, G. Gobsch, C. Buerhop-Lutz, C. J. Brabec, V. Dyakonov, "Quality control of polymer solar modules by lock-in thermography", Journal of Applied Physics, 2010, 107, 014505. CrossRef J. Bachmann, C. Buerhop-Lutz, C. Deibel, I. Riedel, H. Hoppe, C. J. Brabec, V. Dyakonov, "Organic solar cells characterized by dark lock-in thermography", Solar Energy Materials and Solar Cells, 2010, 94, 642-647. CrossRef A. Różycka, K. A. Bogdanowicz, N. Górska, J. Rysz, M. Marzec, A. Iwan, R. Pich, A. Januszko, "Influence of TiO2 Nanoparticles on Liquid Crystalline, Structural and Electrochemical Properties of (8Z)-N-(4-((Z)-(4-pentylphenylimino)methyl)benzylidene)-4-pentylbenzenamine", Materials, 2019, 12, 1097. CrossRef M. L. Petrus, R. K. M. Bouwer, U. Lafont, S. Athanasopoulos, N. C. Greenham, T. J. Dingemans, "Small-molecule azomethines: organic photovoltaics via Schiff base condensation chemistry", Journal of Materials Chemistry A, 2014, 2, 9474-9477. CrossRef K. A. Bogdanowicz, A. Iwan, "Symmetrical Imines with Trirphenylamine Core and the Method of Obtaining Thereof.", March 11th 2019, patent application P.429044. DirectLink K. P. Korona, T. Korona, D. Rutkowska-Zbik, S. Grankowska-Ciechanowicz, A. Iwan, M. Kamińska, "Polyazomethine as a component of solar cells-theoretical and optical study", Journal of Physics and Chemistry of Solids, 2015, 86, 186-193. CrossRef